1992
DOI: 10.1063/1.463166
|View full text |Cite
|
Sign up to set email alerts
|

Magic numbers in (NO)+mArn heteroclusters produced by two-photon ionization in a supersonic expansion

Abstract: Mixed clusters of the form (NO)mArn(m ≤ 4,n ≤ 22)are produced in a supersonic expansion and photoionized by nonresonant two-photon absorption of 266 nm photons. The ions are subsequently separated and detected by time-of-flight mass spectrometry. Anomalously large relative intensities are observed for the cluster ions, NO+Arn(n= 12,18,22) and (NO)2+Arn(n = 17,21), and are attributed to extra stability of these ions. These ‘‘magic numbers’’ at (m+n)=13,19,23 are compared to those observed in rare gas clusters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 54 publications
2
25
1
Order By: Relevance
“…The peaks for n = 12 and 18 are prominent, suggesting that 12 and 18 are "magic numbers" that indicate a particularly stable cluster geometry. 42,43 The same magic numbers are also observed in O − (Ar) n and correspond to the closing of the solvation shell in an icosahedral (12 Ar atoms) and double icosahedral (18 Ar atoms) structure. 24 Similar solvation shell arrangements likely account for the peak intensities observed for n = 12 and 18 in the OH − (Ar) n mass spectrum.…”
Section: A Anion Solvation: Oh − (Ar) Nmentioning
confidence: 52%
“…The peaks for n = 12 and 18 are prominent, suggesting that 12 and 18 are "magic numbers" that indicate a particularly stable cluster geometry. 42,43 The same magic numbers are also observed in O − (Ar) n and correspond to the closing of the solvation shell in an icosahedral (12 Ar atoms) and double icosahedral (18 Ar atoms) structure. 24 Similar solvation shell arrangements likely account for the peak intensities observed for n = 12 and 18 in the OH − (Ar) n mass spectrum.…”
Section: A Anion Solvation: Oh − (Ar) Nmentioning
confidence: 52%
“…4 Briefly, the isentropic core of a pulsed supersonic expansion is selected by a skimmer and intersected at 90°with a focused laser beam. The mass-to-charge ratios of the ions which are formed are analyzed using a linear time-of-flight mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last several years we have utilized resonant and nonresonant MPI and time-of-flight (TOF) mass spectrometry to study homogeneous and binary molecular clusters produced in pulsed gas expansions which contain a variety of inorganic, organic, and organometallic molecules. [3][4][5][6][7][8][9][10][11] Various types of reactions can be photochemically initiated in such clusters. Excitation to dissociative states can yield fragmentation of either the neutral or ion chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Also, this cationic cluster was studied by multiphoton ionization and photodissociation by Dessai et al 22,33 The mixed clusters of the form (NO) m Ar n (m ≤ 4, n ≤ 22) are produced in a supersonic expansion and photoionized by nonresonant two-photon absorption of 266 nm photons and their ions are subsequently separated and detected by time-of-flight spectroscopy. Dessai et al 22 showed that NO + Ar n clusters have extra stability at n = 12, 18, and 22 (referred to there as magic numbers). Later on, these authors extended their work to investigate the (NO + ) m Ar n clusters with m ≤ 7 and n ≤ 54, 33 identifying n = 54 as an additional magic number.…”
Section: Introductionmentioning
confidence: 99%